Synthesis, Characterization, Antimicrobial Activity and DNA Studies of Novel Schiff’s Base Complexes of Some Transition Metal Ions - Ibrahim Sheriff, A.K.; Syed Shafi, S. (Asian Journal of Chemistry, 2011)
A bidentate chelating Schiff base (L) and its complexes with Fe(II), Co(II), Ni(II), Cu(II) and Ru(III) metal ions have been synthesized and characterized by elemental analysis, IR, 1H NMR and 13C NMR spectral studies. The cyclic voltammetric studies were carried out to understand the redox characteristics of some of these complexes. EPR spectral studies and calculation of LFSE, 10Dq, b and μeff have been carried out to prove the existence of covalency in the M-L bond. Interactions of these complexes with calf thymus DNA were investigated by UV-visible absorption spectroscopy and gel electrophoresis. Antimicrobial activity of these compounds have also been studied.